Gastroschisis: A multi-centre comparison of management and outcome - Joanna Manson; Emmanuel Ameh; Noel Canvassar; Tiffany Chen; A Van den Hoeve; F Lever; Afua Hesse; Alastair Millar; Sherif Emil; Niyi Ade-Ajayi (Wolters Kluwer Medknow Publications, 2012)
Background: Anecdotal evidence and a handful of literature reports suggest that the outcome for infants born with gastroschisis in many African countries is poor when compared to Western nations. We wished to evaluate current management strategies and outcomes in African and Western units that treat infants with gastroschisis. Patients and Methods: We conducted a retrospective review of case-notes for infants with gastroschisis who presented to a hospital between 1 January 2004 and 31 December 2007. There were five participating centres, divided for analysis into an African cohort (three centres) and a Western cohort (two centres). Results: Fewer infants presented to a hospital with gastroschisis in the African cohort when compared to the Western cohort, particularly when the size of catchment area of each hospital was taken into account. The physiological state of the infant on presentation and management strategy varied widely between centres. Primary closure, preformed silo and surgical silo with delayed closure were all utilised in the African cohort. Use of the preformed silo and delayed abdominal wall closure was the strategy of choice in the Western cohort. The 30-day mortality was 23% and 1% respectively. This primary outcome measure varied considerably in the African cohort but was the same in the two Western units. Conclusions: Gastroschisis in the African cohort was characterised by fewer infants presenting to a hospital and a more variable outcome when compared to the Western cohort. A detailed epidemiological study to determine the incidence of gastroschisis in African countries may provide valuable information. In addition, interventions such as prompt resuscitation, safe neonatal transfer, the use of the preformed silo and parenteral nutrition could improve outcomes in infants with gastroschisis.